Influence of Inlet Angle of Guide Vane on Hydraulic Performance of an Axial Flow Pump Based on CFD - Lei Xu; Dongtao Ji; Wei Shi; Bo Xu; Weigang Lu; Linguang Lu (Shock and Vibration)
Axial flow pump has been widely used in hydraulic engineering, agriculture engineering, water supply and sewerage works, and shipbuilding industry. In order to improve the hydraulic performance of pump under off-design working conditions, the influence of the inlet segment axial chord and inlet angle adjustment of the guide vane on the pump segment efficiency and flow filed was simulated by using the renormalization group (RNG) k−ε turbulent model based on the Reynolds-averaged Navier–Stokes equations. The results indicate that the inlet segment axial chord and inlet angle adjustment of guide vane have a strong influence on the pump segment efficiency. Considering the support function and hydraulic loss of the guide vane, the inlet segment axial chord is set to 0.25 times the axial chord of guide vane. On the basis of the inlet angle of the guide vane under design conditions, when the inlet segment angle is turned counterclockwise, the pump segment efficiency is improved in the lower flow rate region; moreover, the pump segment efficiency is improved in the larger flow rate region when the inlet segment angle is turned clockwise. As the conditions deviate from the design working conditions, the influence of the guide vane inlet angle on the pump segment efficiency increases. If the inlet segment angle is properly adjusted under off-design working conditions, the flow pattern in the guide vane is improved and the hydraulic loss is decreased, because the inlet segment angle matches with the flow direction of impeller outlet; consequently, the pump segment efficiency is increased.